A COLLABORATION OF NURSES AND DOCTORS IN THE INPATIENT ROOM AT ARIFIN ACHMAD GENERAL HOSPITAL OF RIAU PROVINCE: KOLABORASI PERAWAT DOKTER DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - yecy anggreny; Henny Lucyda; Vionalisa Vionalisa (STIKes Hang Tuah Pekanbaru, 2019)
collaboration is a form of collaboration between nurses and doctors for the same purpose of providing health services in order to increase patient recovery efforts. collaboration between nurses and doctors is limited to recording the doctor's instructions given without discussing and giving opinions or suggestions about the patient's health problems. the result of this study was to identify collaboration between nurses doctors in the inpatient hospital Arifin Ahmad Riau. this type of research is quantitative with descriptive design. the population in this research are all nurses in the inpatient room 196 nurses as populations. the type of samlping technique used in this research was purposive sampling. data collection tools using questionnaires with data processing using computerization and data analysis is done univariately. the results showed that more than half the population (66.8%) of nurses stated that the collaboration of nurses and doctors was not good. based on the results of this study it is suggested to nurses to improve the education, knowledge, and competence of nurses in the implementation of nursing care